Method of construction approximating curves for evaluation and prediction for level of flood waters - Клапоущак, Оксана Ігорівна (Eastern-European Journal of Enterprise Technologies, 2014)
The developed method for predicting the flood water level allows to analyze statistical data from meteorological stations (precipitation, humidity deficit and wind speed) to predict the water level in rivers during floods. The method for constructing approximating curves was performed on the basis of statistical data on the Prut River level and meteorological data (precipitation amount, air humidity and wind speed) from meteorological stations in the cities of Yaremcha, Kolomyia and Chernivtsi during the flood waters from 24.07.08/03 to 25.07.08/15. The obtained results and the proposed method will allow to predict flood waters, and the more data from meteorological stations the more accurate the weather forecast that will allow to reduce economic costs and avoid casualties during flood waters. Currently, studies of the influence of one meteorological data on the other, and their impact on rising the water level in rivers using contingency factor are carried out. Having revealed the correlation of data from meteorological stations and data on the water rise level, further studies will be directed at determining the model adequacy. However, the proposed model has confirmed the fact that the 100 m/house and more [18] cause catastrophic river water level rise, and also gives grounds to confirm the model adequacy.